U-Pb age distribution recorded in zircons from Archean quartzites in the Mt. Alfred area, Yilgarn Craton, Western Australia - Kielman, R.; Nemchin, Alexander; Whitehouse, M.; Pidgeon, Robert; Bellucci, J. (Elsevier BV, 2018)
The U-Th-Pb isotopic data from detrital zircon grains from five samples of Archean quartzite from the Mt. Alfred area of the Illaara greenstone belt in the Yilgarn Craton of Western Australia are presented in this study. The zircon grains are typically fractured and contain both irregular and oscillatory zoned internal structures as revealed by cathodoluminescence imaging. Concordant 207 Pb/ 206 Pb ages range between 3109 ± 17 and 3918 ± 16 Ma (2s), with three main age peaks at ca. 3640, 3690 and 3760 Ma. Older 207 Pb/ 206 Pb ages up to 4067 ± 5 Ma are strongly affected by at least one recent disturbance event, however one single-grain discordia yields an upper intercept age of 4107 ± 12 (MSWD = 1.2). A further sixteen zircon grains with multiple analyses define discordia that suggest U-Pb disturbance events in the Neoarchean and the Mesozoic, the latter as a result of invasive low temperature weathering solutions. The notable lack of grains with ages less than ~3.6 Ga in the Mt. Alfred detrital zircon population differentiates it from other quartzite samples from both the Illaara Formation and the Eoarchean zircon-bearing metasedimentary rocks of the Narryer Terrane. Also, the limited spread of zircon ages between 3640 and 3760 Ma suggests a relatively uniform and possibly local source region. However, no rocks of this age have been found in the Youanmi Terrane. This implies either the distal transport of similarly aged clastic sediments at 3.1 Ga from the Narryer Gneiss Complex (NGC) to the Mt. Alfred area, or the previous existence of NGC-like rocks near the Illaara greenstone belt that are either not currently recognised or have since been destroyed.